Identification of DNAH17 Variants in Han-Chinese Patients With Left–Right Asymmetry Disorders - Yu, Xuehui; Yuan, Lamei; Deng, Sheng; Xia, Hong; Tu, Xiaolong; Deng, Xiong; Huang, Xiangjun; Cao, Xiao; Deng, Hao (Frontiers in Genetics, 2022)
The formation of left-right asymmetry of the visceral organs is a conserved feature of human body, and the asymmetry specification of structure and function is precisely orchestrated by multiple regulatory mechanisms. The abnormal results of organ positioning situs arise from defective cilia structure or function during embryogenesis in humans. In this study, we recruited two unrelated Han-Chinese families with left-right asymmetry disorders. The combination of whole exome sequencing and Sanger sequencing identified two compound heterozygous variants: c.4109C>T and c.9776C>T, c.612C>G and c.8764C>T in the dynein axonemal heavy chain 17 gene (DNAH17) in two probands with left-right asymmetry disorders. We report for the first time a possible association between DNAH17 gene variants and left-right asymmetry disorders, which is known as a causal gene for asthenozoospermia. Altogether, the findings of our study may enlarge the DNAH17 gene variant spectrum in human left-right asymmetry disorders, and pave a way to illustrate the potential pathogenesis of ciliary/flagellar disorders and provide supplementary explanation for genetic counseling.